Bridging Tradition and Technology: Gamification in Modern Islamic Boarding Schools - Nadiatul Maziyyah Attarwiyah; Indah Rizqiyatul Wasi’ah; Siti Nurul Jennah (Al-Qalam Institute, 2025)
This study aims to analyze the implementation strategy of gamification in Islamic boarding school education as an innovative effort to increase students' learning motivation at the Al-Qodiri 02 Islamic Boarding School. This study uses a qualitative approach with a case study method, where data is collected through non-participant observation, in-depth interviews, and documentation. The data validation process was carried out through focus group discussions (FGD) involving several online and offline participants. The results of the study indicate that the implementation of gamification elements, such as the point system, levels, badges, and leaderboards, increased the involvement and motivation of students in the learning process. In addition, the gamification integration strategy, which involved the leadership of the boarding school as the main driver, succeeded in creating a more dynamic and engaging learning atmosphere. This study provides important implications on how gamification can be integrated with the Islamic boarding school education approach to support learning relevant to technological developments and improve the overall quality of learning.